Treatments for brain metastases from EGFR/ALK-negative/unselected NSCLC: A network meta-analysis - Zhang Chengkai; Zhou Wenjianlong; Zhang Dainan; Ma Shunchang; Wang Xi; Jia Wang; Guan Xiudong; Qian Ke (Open Medicine, 2023)
More clinical evidence is needed regarding the relative priority of treatments for brain metastases (BMs) from EGFR/ALK-negative/unselected non-small cell lung cancer (NSCLC). PubMed, EMBASE, Web of Science, Cochrane Library, and ClinicalTrials.gov databases were searched. Overall survival (OS), central nervous system progression-free survival (CNS-PFS), and objective response rate (ORR) were selected for Bayesian network meta-analyses. We included 25 eligible randomized control trials (RCTs) involving 3,054 patients, investigating nine kinds of treatments for newly diagnosed BMs and seven kinds of treatments for previously treated BMs. For newly diagnosed BMs, adding chemotherapy, EGFR-TKIs, and other innovative systemic agents (temozolomide, nitroglycerin, endostar, enzastaurin, and veliparib) to radiotherapy did not significantly prolong OS than radiotherapy alone; whereas radiotherapy + nitroglycerin showed significantly better CNS-PFS and ORR. Surgery could significantly prolong OS (hazard ratios [HR]: 0.52, 95% credible intervals: 0.41–0.67) and CNS-PFS (HR: 0.32, 95% confidence interval: 0.18–0.59) compared with radiotherapy alone. For previously treated BMs, pembrolizumab + chemotherapy, nivolumab + ipilimumab, and cemiplimab significantly prolonged OS than chemotherapy alone. Pembrolizumab + chemotherapy also showed better CNS-PFS and ORR than chemotherapy. In summary, immune checkpoint inhibitor (ICI)-based therapies, especially ICI-combined therapies, showed promising efficacies for previously treated BMs from EGFR/ALK-negative/unselected NSCLC. The value of surgery should also be emphasized. The result should be further confirmed by RCTs.